Diastereoselective synthesis of fluoroisosteric analogues of antiparasitic pyrrolobenzoxazine alkaloids from tryptophan by successive fluorination–cyclization and a Meisenheimer-type rearrangement. Issue 9 (7th June 2017) - Das, Biplab Kumar; Tokunaga, Etsuko; Harada, Kyosuke; Sumii, Yuji; Shibata, Norio
Abstract : Fluoroisosteric analogues of an antiparasitic pyrrolobenzoxazine alkaloid CJ-12663 were designed and diastereoselectively synthesized. Abstract : Fluoroisosteric analogues of an antiparasitic pyrrolobenzoxazine alkaloid CJ-12663 were designed and diastereoselectively synthesized by successive fluorination–cyclization and a Meisenheimer-type rearrangement from tryptophan in good yields.